Comparative analysis of the gut microbiota composition among three captive hornbills - Yang, Enmei; Wang, Song; Feng, Huajuan; Zheng, Fanglin; Duan, Yubao; Yang, Shuang (Frontiers in Microbiology, 2025)
This study investigated the gut microbiota of three captive hornbill species (Anthracoceros albirostris, Buceros bicornis, Rhyticeros undulatus) at the Nanning Zoo. Fecal samples were aseptically collected from 30 hornbills, and 16S rRNA high-throughput sequencing was employed to analyze the composition, diversity, and potential functions of the gut microbiota. The influence of host taxonomic status, sex, and captive environment on the gut microbiota was explored. The results revealed that the dominant phyla in the gut microbiota of all three hornbill species were Proteobacteria, Firmicutes, Actinobacteria, and Bacteroidetes. Although no significant differences were detected in the gut microbiota composition among different species and sexes, LEfSe analysis indicated significant enrichment of Erysipelotrichaceae and Lactobacillus_hayakitensis_DSM_18933_JCM_14209 in the Oriental Pied Hornbill group, as well as Clostridiales, Paenibacillaceae, and Paenibacillus_xylanilyticus in the Great Hornbill group. PICRUSt analysis indicated that the functional genes of the gut microbiota in all three hornbill species were primarily enriched in metabolic pathways, showing similar relative abundances. This study suggests that the gut microbiota characteristics of hornbills align with those of omnivorous birds. The homogenization of food resources in a captive environment may weaken the impact of host differences on the gut microbiota. The research findings provide a scientific basis for the health management of captive hornbills and the microecological assessment of wild population habitats.